(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
pH measurement of the gastrointestinal tract is an important method for diagnosing various diseases of the gastrointestinal tract. It allows you to determine the level of acidity in the stomach and intestines, which can be useful for identifying various pathologies, such as gastritis, peptic ulcers, reflux esophagitis, digestive dysfunction and others.